The Using of Protected Fatty Acid Supplement to Improve Carcass Percentage of Broiler Chicken - Auza, Fuji Astuty; Tasse, A. M.; Salido, W. L.; Napirah, A. (Proceeding INTERNATIONAL SEMINAR IMPROVING TROPICAL ANIMAL PRODUCTION FOR FOOD SECURITY)
The research was aimed to know the percentage carcass of broiler with rationsupplementation of protected fatty acid. The sample used in this research is 48 broiler chickensunsexed strain avian CP707 production of PT. Charoen Phokhpand Makassar divided in 12 plotsenclosure 1x1 meters. The design of this research is a Completely Randomized Design with 3treatments and 4 replications. The treatments were T0 = commercial ration BP-11, T1 = T0+3% drycarboxylate salt mixed (DCM), T2-T0+3% coconut oil hydrolisate. Variables measured were weightgain (kg), weight carcass (kg) and percentage carcass (%). Data were analyzed by variance analysisand continued by orthogonal contrast test. The conclusion showed that (1) ration withsupplementation 3% dry carboxy late salt mixed give result 2,00±0,04 kg weight gain, 1,34±0,05 kgweight carcass and 66,88±2,19% percentage carcass, (2) ration with supplementation 3% coconut oilhydrolisate give result 1,91±0,05 kg weight gain, 1,29±0,0,07 weight carcass and 67,28±2,29%percentage carcass, (3) ration with 3% supplementation of protected fatty acid cannot improveweight gain, weight carcass and percentage carcass broiler chicken.Key Words : Fatty Acid, Weight Gain, Weight Carcass, Percentage Carcass, Chicken Broiler